Cre recombinase-mediated inversion using lox66 and lox71: method to introduce conditional point mutations into the CREB-binding protein - Zhang, Zuwen (Oxford University Press, 2002)
CREB-binding protein (CBP) is a multifunctional cofactor implicated in many intracellular signal transduction pathways. We aimed to investigate the involvement of CBP in the cAMP response element-binding protein (CREB)-mediated pathway. The point mutation Tyr658Ala in the CREB-binding domain (CBD) was shown to abolish the binding activity of CBP to phospho-CREB, the activated form of CREB. By using a mutant Cre/loxP recombination system, this point mutation was aimed to be generated in the mouse genome in a tissue- and time-specific manner. A targeting construct in which CBD exon 5 and inverted exon 5* containing the point mutation flanked by two mutant loxP sites (lox66 and lox71) oriented in a head-to-head position was generated. When Cre recombinase is present, the DNA flanked by the two mutant loxP sites is inverted, forming one loxP and one double mutated loxP site. As the double mutated loxP site shows low affinity for Cre recombinase, the favorable reaction leads to a product where the mutated exon 5* is placed into the position to be correctly transcribed and spliced. Inversion was observed to be complete in both bacteria and mouse embryonic stem cells. Our results indicate that this Cre- mediated inversion method is a valuable tool to introduce point mutations in the mouse genome in a regulatable manner.